A STUDY ON CONCRETE USING SAP AS AN INTERNAL CURING AGENT FOR WATER CEMENT RATIOS HIGHER THAN 0.4 - Anamika, G.; Nizar, N.Mohamed (IJRDO - Journal of Mechanical And Civil Engineering, 2015)
Proper curing of concrete is necessary so that the concrete ensures intended performance and durability requirements. Internal curing refers to the process by which the hydration of cement occurs because of the availability of additional internal water that is not part of the mixing Water. Conventionally, curing concrete means creating conditions such that water is not lost from the surface i.e., curing is taken to happen ‘from the outside to inside’. Proper curing of concrete structures is important to ensure that they meet their intended performance and durability requirements. Therefore an effective in situ curing is necessary to maximize the degree of hydration and to minimize the cracking problems due to drying shrinkage. Concrete is accompanied with evaporation, loss of internal relative humidity, early age cracking and eventually loss of strength. This project is to add super absorbent polymer to concrete at various proportions. In this study, the effect of internal reservoirs as agent for internal curing (Various volume fraction and various aspect ratios) on the short term and long term engineering properties of concrete will be investigated.